Are older drivers getting the information they need from their health care provider? - Huseth-Zosel, Andrea L. (International Journal Of Community Medicine And Public Health, 2018)
Background: The number of drivers aged 65 or older is expected to increase, creating a significant public health issue. Health care providers (HCPs) can provide counseling to their older patients to assist with continuing to drive safely. The goal of the current study was to determine the frequency with which older drivers recall having had received driving-related information from their HCP. Methods: Current and former drivers aged 65 or older in the upper Midwest were surveyed about whether a HCP had provided information to them about driving issues. Results: Of the 59 completed responses for former drivers, less than 15% reported having received information from their HCP on driving issues prior to stopping driving. Of the 775 completed responses for current drivers, 0.7% of respondents aged 65 to 74, 0.4% of respondents aged 75 to 84, and 7.0% of respondents aged 85 or older recalled their HCP ever having provided them with information about safe driving habits, or been told they should limit or discontinue their driving. Conclusions: Few adults aged 65 or older are receiving information related to driving safety from their HCP. HCP conversations are an important part of normalizing the transition through the stages of driving cessation, and may assist older adults get prepared, both emotionally and logistically, for the time when they have to stop driving. Additional research on HCP provision of driving safety information to older adults is needed.